GMSK modulator implementation for earth explorations satellite service / Rasidi Nordin @ Radin - Nordin @ Radin, Rasidi (2013)
Due to restriction of the spectrum for Earth Exploration Satellite Service (EESS) at 8.5 GHz X-Band allocation, the mission for EESS are looking higher order modulation scheme instead of traditionally phase shift keying (PSK) such as Quadrature Phase Shift Keying (QPSK), Offset Quadrature Phase Shift Keying (OQPSK) and 8-PSK. The main problems with the current modulation are the Bandwidth efficiency and the Inter-symbol Interference Tolerance. The objectives of this research are to analyze Gaussian Minimum Shift Keying (GMSK) perform in EESS, to identify the best BT value for better GMSK performance, to analyze the filtering effect to bandwidth (BW) in GMSK, to simulate GMSK in satellite communication using Matlab and to compare the performance of GMSK with the OQPSK filtering with square root raised cosine (RRC) in satellite communication. The methodology used in this study is identify the current OQPSK with RRC filtering method used such as the roll-off factor best value and its Bit Error Rate performance, designed and simulate the GMSK modulation by using the same method used in OQPSK in Matlab and finally compare the simulation result of GMSK with the OQPSK filtered with RRC. Besides, the BER performance is checked using the BER Tools in Matlab. The result shows that the GMSK performance is almost same as OQPSK in term of bit error rate (BER). However, the GMSK performance in terms of bandwidth efficiency is better compare to the OQPSK. Moreover, spectrum density shows that the GMSK gives constant sidelobe power. In conclusions, the GMSK could be used at lower data rates with a performance almost similar to the OQPSK filtered with RRC.